PENERAPAN MODEL PEMBELAJARAN PROBING PROMPTING BERBANTUAN MEDIA FLASH CARD UNTUK MENINGKATKAN HASIL BELAJAR IPS TERPADU SISWA KELAS VIII MTsN 3 LHOKNGA ACEH BESAR - Fazri, Fazratul Ulfa; Abdi, Abdul Wahab; Yulianti, Fitriani (Jurnal Ilmiah Mahasiswa Pendidikan Geografi, 2024)
The Probing Prompting learning model is a method that involves a series of questions posed by the teacher to guide and explore students' understanding. This approach encourages students to connect their prior knowledge with previous experiences, enabling them to construct new concepts independently. Flash Cards are used as visual aids to clarify materials and enhance students' memory retention. This study aims to analyze the improvement in student learning outcomes, teacher and student activities, teachers' teaching management skills, and students' responses to this learning model. The subjects of this study were 30 students of class VIII-1 at MTsN 3 Aceh Besar. Data collection was conducted through pre-tests and post-tests, observation of teacher and student activities, evaluation of teachers' teaching management skills, and student response questionnaires. The data were analyzed using descriptive percentage statistics. The results showed that individual mastery increased from 30% in cycle I to 50% in cycle II and 90% in cycle III. Meanwhile, classical mastery improved from 10% in cycle I to 40% in cycle II and 80% in cycle III. Teacher and student activities increased from 4 activities in cycle I to 10 in cycle III. Teachers' teaching management skills also improved from a moderate category (2.53) to a better level (3.47). Additionally, 83.3% of students responded positively, stating that the Probing Prompting model assisted their understanding and made learning more enjoyable. Thus, this model has proven effective in enhancing student learning outcomes.